IPGP laboratory data on granular flows' high-frequency seismic signals - Arran, Matthew Iain; Mangeney, Anne; de Rosny, Julien; Farin, Maxime; Toussaint, Renaud; Roche, Olivier (PANGAEA, 2020)
Data from laboratory experiments in which glass beads flowed, via an opening of a given height $h_g$, into and through a channel at a given incline $\tan θ$. Over the duration of each experiment, we recorded: 1) the mass outflow from the channel; 2) the voltage outputs of i) a force sensor and ii) accelerometers, fixed to an instrumented plate in the channel's base; and 3) images of the flow, captured through the channel's transparent side wall by a high-speed camera. The analysis of voltage outputs and high-speed camera images was calibrated by i) measuring the force sensor's responses to a fixed vertical load, ii) examining the accelerometers' responses to vertical impacts of individual glass beads, and iii) capturing images of a checked calibration pattern and of static beads. Data here comes from these calibration measurements, an experiment at $h_g = 20$ mm and $\tan θ = 0.44$, and another at $h_g = 28$ mm and $\tan θ = 0.52$. The full 340 GB of data, from three experimental repeats at each of 19 combinations of $h_g$ and $\tan θ$, will be available from the authors until at least 2025, care of Anne Mangeney.
Keywords: Granular flow; Laboratory experiment; Seismic signal